Destructive Fishing in Coremap II area, Raja Ampat - Sila, Ridwan; Kabera, Yuanike; Rumereb, Victor (Journal of Indonesian Coral Reefs, 2011)
Raja Ampat located in West Papua province is well know as region that has high diversity of marine life, particularly corals and coral fishes. Manu parts of the coastal and marine areas in the regios have been protected through the development of marine protected areas (MPAs). It has been known that destructive fishing has been one of the cause of the destruction of coral and marine life. The present study aims to identify the existence of the illegal fishing pratice by conducting a field survey using observatory and interview techniques, As many as 102 fishers from 10 villages were interviewed. The results of the study revealed that prominent existed destructive fishing was the use of explosive materials (fish bomb) by fisher from outside the Coremap areas (especially from Sorong). Local fisher used fishing gears, such as spears and handlines to catch fish in coral reefs in wich the impacts on coral may be minimal. Several factors that may sustain destructive fishing practice existing in the Coremap areas were ineffectiviness of monitoring, controlling, and surveylance (MCS) by government and localcommunity, lack of law enforcement and low economic capacity of community